2.4 GHz SQUARE RING PATCH WITH RING SLOT ANTENNA FOR SELF INJECTION LOCKED RADAR - Irfan Mujahidin; Basitha Febrinda Hidayatulail; Putri Surya Arinda (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2019)
Abstract: The radar network system requires high-cost frequency, the complex configuration component of the electromagnetic feeding network circuit to make four output antenna with the same power and different phase output specifically for SIL (Self Injection Locked) Radar, and inexpensive material, especially for the electromagnetic component. 2.4 GHz Square Ring Patch with Ring Slot Microstrip Antenna with four output that has the same power using power divider and 90-degree phase different output for SIL Radar. this is the novel shaped microstrip Antenna with the free frequency, more unassuming configuration, and inexpensive material at the 2.4 GHz for SIL Radar. This system is an important part component of SIL Radar that is package consists of a 2.4 GHz Microstrip antenna with the Square Ring Patch with Ring Slot, double power divider which is double input with quad output with the same power and directional coupler 90-degree phase difference with two input and two output. The Antenna has single band and narrow bandwidth with the frequency is 2.38 GHz until 2.43 GHz under -10dB S parameter and frequency resonance 2.4 GHz, the radiation pattern is directional and the gain is 8.37 dBi, The Power divider has S parameter 2 port output of one part under -20dB at 2.4 GHz and isolation above -4dB that is all good agreement. The 90-degree hybrid coupler has S35 of -35.95dB, S46 of 35.09, S53 of -3.47, and S64 of -3.39 that all is qualified good operation. And overall size of the proposed antenna system is 100 mm times 55.7 mm with FR4 (Phenolic White Paper) with a dielectric constant is 4.4 that has 50ohm.DOI : https://doi.org/10.26905/jeemecs.v2i2.3253